Environmental knowledge, attitudes and behavior of higher education students: a case study in Portugal - Sousa, Sara; Correia, Elisabete; Leite, Joana; Viseu, Clara (International research in geographical and environmental education, 2021)
The main purpose of this research study is to explore higher education students' environmental knowledge, attitudes and behavior. To achieve this goal, a questionnaire was conducted among the students of a public higher education institution (HEI) in Portugal. Our findings result from 371 valid responses and allow us to conclude that most students have significant environmental knowledge, have environmentally friendly attitudes and are environmentally responsible in the areas of use of paper, recycling and energy consumption. Results also indicate that most students are aware of the importance of protecting the environment and consider themselves well informed about environmental issues. Students' main information sources of environmental information are television, social networks and the HEI they attend. We conclude that more attention should be given to HEIs, due to their significant potential to educate and train future decision makers in a society, to enhance a more protective approach to the environment.